Budujemy nowoczesną Polskę - Markowicz, Andrzej (1942- ).; Stocznia Gdańska im. Lenina (Gdańsk : Stocznia Gdańska im. Lenina, 1974)
Plakat propagandowy.
Keywords: Propaganda -- Polska -- 1970-2000 -- plakaty; Gdańsk (Polska) -- 1970-2000 -- plakaty